율곡 철학의 근대성과 탈근대성 - 지각론과 수양론을 중심으로 - 김우형; Kim Woo Hyung (Yulgok sasang yŏn'gu, 2022)
본고는 율곡(栗谷) 이이(李珥, 1536-1584)의 철학에 함유되어 있는 근대성의 요소들을 살펴보고, 또한 근대성과 대비되는 탈근대적인 성격들은 어떤 것들이 있는지 고찰한 것이다. 이이는 이황의 호발설(互發說)을 비판하면서 기발이승일도설(氣發理乘一途說)을 제기하였고, 새로운 인심도심론을 구성하였다. 기발이승일도설은 자연주의적, 경험론적, 질료중시적, 심리학적 특성을 띤다는 점에서 주기(主氣)론이라 할 수 있다. 인심과 도심은 주관적 지각내용에서 구분되는 것이 아니라, 감정의 결과가 외적 규범과 일치하는지 여부에 따라 판정된다는 객관주의, 결과주의 윤리설의 입장으로 설명된다. 율곡 철학의 이러한 주기론적 지각론과 인심도심론은 주리(主理)론과 더불어 근대성의 두 축을 이룬다고 할 수 있다. 율곡 철학이 지니는 탈근대성(현대성)은 질료적인 기(氣)가 인간과 천지만물에 관통해 있다는 자연주의의 입장에서 설명한 변화기질(變化氣質)의 수양론에서 발견된다. 그것의 함의는, 사회적 지도층의 경우 지각 기능의 고양과 학문을 통해 도덕 실천을 성인의 경지로 끌어올리는 노력을 할 필요가 있다는 것이고, 일반인의 경우 비단 자신의 직무적 능력뿐만 아니라 주요한 성격적인 덕을 평생에 걸쳐 점진적으로 변화시켜서 긍정적으로 개선시킬 수 있다는 것이다. This paper examines the elements of modernity contained in Yulgok Yi I (1536-1584)’s philosophy, and also researches what are the post-modern characteristics that contrast with modernity. While Yi I criticized Yi Hwang’s theory of li-gi mutual issuance (理氣互發說), he raised the gi-issuance-only theory (氣發理乘一途說) forming a new theory of Human-Mind and Moral-Mind (人心道心論). His gi-issuance-only theory can be said to be gi-centered position (主氣) in that it has naturalistic, empirical, material-oriented, and psychological inclination. It can be explained as the ethical perspective of objectivism and consequentialism in that Human-Mind and Moral-Mind cannot be distinguished by subjective perceptual contents in consciousness but determined by whether the results of emotions are consistent with external norms. The gi-issuance-only theory and the theory of Human-Mind and Moral-Mind of Yulgok philosophy can be said to form the two axes of modernity along with the li-centered (主 理) epistemological position. The post-modern characteristics of Yulgok philosophy is found in the self-cultivation theory, especially his view on temperament change (氣質變化), which is explained from the perspective of naturalism in which matter-energy penetrates human beings, heaven-and-earth and myriad-things. The implication of his self-cultivation theory is as follows: Social leaders need to make efforts to raise moral practice to the level of sages by enhancing cognitive functions and learning, while general public can gradually improve not only their job ability but also their major character virtues.